Postoperative changes in serum cytokines profile and nitric oxide levels in patients with cystic echinococcosis - Refik M.; Mehmet N.; Durmaz R. (Parasite, 2005)
The aim of the present study was to examine serum cytokines and nitric oxide (NO) levels in patients with cystic echinococcosis (CE). 28 patients with CE were studied and all underwent surgery. Serum levels of tumour necrosis factor-alpha (TNF-α), interleukin IL- 1β, receptor of soluble IL-2R (sIL-2R), IL-6, IL-8, nitrate/nitrite, and C-reactive protein (CRP) were determined before and after induction of treatment. Data were compared with those obtained from 28 healthy volunteers. IL-6 was elevated in all CE patients (100%). IL-8 was increased in 11/28 (39.3%). Increased levels of IL-2R and TNF-α were found in a limited number of them particularly those showing cysts in the central area of the liver (5/28, 6/28). IL-1β level was not elevated in any patient except in secondary severe CE. CRP and nitrate/nitrite levels were also increased. A positive correlation between CRP and IL-6 (r = 0.74; p < 0.001) was found confirming the link between inflammation due to CE and activation of monocytes. All patients completely recovered and the levels of the studied parameters reverted to normal levels except one patient in whom severe recurrent disease occurred two years after the first operation. These results suggest that there are different immunoregulatory events and cytokines response during CE and may be in part related to slight monocytosis and in part to Th2 activation. IL-6, NO and CRP were unambiguously involved in the host parasite interaction and therefore may be useful markers in monitoring CE management and evaluating surgical stress.